2015 Asia-Pacific Microwave Conference (APMC) 2015
DOI: 10.1109/apmc.2015.7413434
|View full text |Cite
|
Sign up to set email alerts
|

A 24-GHz transformer-based stacked-FET power amplifier in 90-nm CMOS technology

Abstract: A 24-GHz transformer-based stacked-FET power amplifier (PA) was designed in 90-nm CMOS technology. The stack configuration overcomes the low breakdown voltages of scaled transistors. The proposed power amplifier achieves a saturated output power of 21.7 dBm and 1-dB compressed output power (OP 1dB ) of 18.9 dBm with peak power-added efficiency (PAE) of 16.7% at 3-V supply voltage. The chip occupies an area of 0.53 × 0.51 mm 2 , including all the dc and RF pads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Owing to the intrinsic drawbacks of standard CMOS process, namely, low breakdown voltage, low power gain (PG), and large substrate loss at high frequency perspectives, the design of a PA at K band in CMOS with satisfactory performance is still a challenging task. Nevertheless, there have been many attempts to design PAs at K band in CMOS over the last decade 6–11 . Joshin et al, adopted the two‐stage cascode configuration and off‐chip Wilkinson power divider and combiner topology for the PA design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the intrinsic drawbacks of standard CMOS process, namely, low breakdown voltage, low power gain (PG), and large substrate loss at high frequency perspectives, the design of a PA at K band in CMOS with satisfactory performance is still a challenging task. Nevertheless, there have been many attempts to design PAs at K band in CMOS over the last decade 6–11 . Joshin et al, adopted the two‐stage cascode configuration and off‐chip Wilkinson power divider and combiner topology for the PA design.…”
Section: Introductionmentioning
confidence: 99%
“…A PA with the transformer‐based stacked‐FET topology was proposed by Alsuraisry et al, in 90‐nm CMOS. The PA achieved OP 1dB of 18.9‐dBm and 11.5‐dB small signal gain 7 . Jen et al, reported a 20 to 24 GHz fully integrated PA with lumped‐element components for matching purpose and cascode structure for gain boosting 8 .…”
Section: Introductionmentioning
confidence: 99%